Forensic parameters and population analysis of 21 autosomal STR loci in the Wuhu Han population from Anhui Province, East China - Yanyan Yang; Qianqian Li; Xinrui Yang; Ziwei Zhang; Yongliang Hu; Yue Zhang; Fang He (Annals of Human Biology, 2024)
Background At present, there are no available genetic data on the AGCU EX22 Kit from the Wuhu Han population.Aim This study investigates the applicability of the AGCU EX22 kit, designed for the Chinese population for forensic analysis and population genetics of the Wuhu Han population.Subjects and methods Bloodstains from 1565 unrelated healthy individuals in Wuhu city, Anhui Province, were collected for analysis. The AGCU EX22 kit was used for amplification, and capillary electrophoresis was used to separate the amplification products. Allele frequencies and forensic parameters were determined. The Wuhu Han population was compared to 10 reference populations through genetic distance, a phylogenetic neighbor-joining tree and principal component analysis.Results In total, 281 alleles and 1187 genotypes were observed. No significant deviations from Hardy-Weinberg equilibrium at any locus were found after Bonferroni’s correction. The 21 autosomal short tandem repeat (STR) genetic markers exhibited high informativeness and polymorphism. The cumulative power of discrimination and power of exclusion were 0.999999999999999999999999913380 and 0.999999996752339, respectively. Population comparisons revealed a genetic affinity between Wuhu Han and southern Han populations, except for the Guangdong Han population, which aligned with the traditional geographical division in China.Conclusion The AGCU EX22 Kit, containing 21 STR loci, is suitable for forensic application and population genetics studies in the Wuhu Han population.